1999
DOI: 10.1136/jcp.52.12.910
|View full text |Cite
|
Sign up to set email alerts
|

A human skin explant model for predicting graft-versus-host disease following bone marrow transplantation.

Abstract: Graft-versus-host disease (GVHD) is the most serious complication following bone marrow transplantation, with an incidence of 40-60%. The disease can be fatal in 50% of cases, even in patients receiving marrow from an HLA identical sibling. Several assays have been developed to try to predict the development of GVHD, including mixed lymphocyte culture reaction, cytotoxic T lymphocyte precursor, and helper T lymphocyte precursor frequency assays. This review describes an in vitro skin explant model which has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…It was prospectively tested as a method to predict GvHD incidence and severity in a donor/patient cohort by Vogelsang et al (1985). Several studies used the skin explant assay to predict the likelihood of acquiring GvHD and reported correlation rates of 80–90% with clinical outcome, which proved the skin explant assay superior to other in vitro models that had been designed for this purpose (Sviland and Dickinson, 1999; Dickinson et al, 2001; Hromadnikova et al, 2001; Sviland et al, 2001; Wang et al, 2006). The accuracy of the prediction by skin explant, however, was dependent on the type of GvHD prophylaxis and conditioning regimens used.…”
Section: The Rat Skin Explant Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…It was prospectively tested as a method to predict GvHD incidence and severity in a donor/patient cohort by Vogelsang et al (1985). Several studies used the skin explant assay to predict the likelihood of acquiring GvHD and reported correlation rates of 80–90% with clinical outcome, which proved the skin explant assay superior to other in vitro models that had been designed for this purpose (Sviland and Dickinson, 1999; Dickinson et al, 2001; Hromadnikova et al, 2001; Sviland et al, 2001; Wang et al, 2006). The accuracy of the prediction by skin explant, however, was dependent on the type of GvHD prophylaxis and conditioning regimens used.…”
Section: The Rat Skin Explant Assaymentioning
confidence: 99%
“…The skin explant closely resembles the histopathology of cutaneous GvHD and allows the study of pathophysiological processes related to GvHR (Sviland and Dickinson, 1999; Dickinson et al, 2001; Dickinson et al, 2002). Histological grading of the skin explant, from grade I to grade IV with increasing severity (Lerner et al, 1974), represents a standardized method to evaluate the risk for selected donor/recipient combinations before transplantation.…”
Section: The Rat Skin Explant Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20] These studies indicate that skin biopsies have been of limited value to confirm or predict the development of systemic GVHD that requires steroid treatment. Our main objective was to investigate with histopathological and immunohistochemical methods whether the source of stem cells might influence the development of GVHD, and thus possibly acquire new insight into the mechanisms involved.…”
mentioning
confidence: 99%
“…Studies in mice have shown that host antigen-presenting cells, in particular dendritic cells, are essential, 15 and the cytokines released by tissue damage upregulate MHC gene products on those cells. 16 One test used skin biopsies from the patient in a co-culture system with lymphocytes from the prospective donor. Minor histocompatibility antigens (miHA) are also presented by MHC molecules.…”
Section: Introductionmentioning
confidence: 99%